Duplication and Multiseptate Urinary Bladder: A Rare Case Report - Zulfikar, Muhammad Fawzi; Djatisoesanto, Wahjoe; Tarmono, Tarmono (Folia Medica Indonesiana, 2021)
The multiseptate bladder is a congenital bladder anomaly that is very rare and often accompanied by other congenital abnormalities. This condition could result in intravesical obstruction and kidney failure in more serious conditions. A 3-year-old girl without any complaint was consulted by the Pediatric Surgery Department with postoperative cloacal type malformation anorectal (MAR) postero-sagittal anorecto-vagino-urethroplasty (PSARVUP) + sigmoidectomy. Magnetic Resonance Imaging (MRI) of the pelvis showed the appearance of four interconnected multiple fluid lesions. Cystoscopy was performed and found many septa with varied positions and forms. From the cystography during the operation, it was seen duplication of the right and left bladder. There was no further operative treatment in the field of urology because no urinary tract obstruction and normal renal function were found in this study.